Increased Peripheral Interleukin 10 Relate to White Matter Integrity in Schizophrenia - Fu, Gui; Zhang, Wenjing; Dai, Jing; Liu, Jieke; Li, Fei; Wu, Dongsheng; Xiao, Yuan; Shah, Chandan; Sweeney, John A.; Wu, Min; Lui, Su (Frontiers in Neuroscience, 2019)
Background: Schizophrenia is characterized by the disruption of microstructural white matter (WM) integrity, while the pathogenesis remains unclear. Inflammation is associated with the WM pathology in schizophrenia. Interleukin 10 (IL-10) has been proved to be related to schizophrenia in both animal and human models. The aim of this study was to explore whether peripheral IL-10 was associated with microstructural WM integrity in schizophrenia. Methods: 47 patients with schizophrenia and 49 healthy controls underwent diffusion tensor imaging and venous blood sampling. Tract-Based Spatial Statistics was conducted to explore the differences in fractional anisotropy (FA), radial diffusivity (RD), mean diffusivity (MD) and axial diffusivity (AD) between patients and controls. Quantitative chemiluminescence assay was performed to measure peripheral IL-10 levels. General linear regression analysis using stepwise method was applied to examine the relationship between peripheral IL-10 and diffusion measures. Results: Compared with controls, peripheral IL-10 levels were higher and significant reduction of FA and AD and increase of RD and MD were observed in patients (corrected p<0.05). Regression analysis revealed that peripheral IL-10 was negatively correlated with FA in the right posterior thalamic radiation and left inferior fronto-occipital fasciculus among schizophrenia patients (β=-0.51, p=0.01; β=-0.47, p =0.02, respectively) but not among healthy controls (β=-0.01, p=0.95; β=-0.003, p =0.98, respectively), and the differences in regression curves were significant (z =2.50, p =0.01; z =2.37, p=0.02, respectively). IL-10 was negatively connected with MD in the right parietal arcuate fasciculus (β=-0.40, p =0.048) and body of the corpus callosum (β=-0.43, p=0.03) across in patients, while not in controls. And the magnitude of correlations in patient and control groups was different (z=2.48, p=0.01 and z=2.61, p<0.01, respectively). In addition, IL-10 was positively associated with RD in the right parietal arcuate fasciculus among patients (β =0.45, p =0.04) but not among healthy controls (β =0.26, p =0.94), but the correlation coefficients were not significant (z =0.98, p =0.32). Conclusion: Our findings demonstrated that elevated peripheral IL-10 levels were associated with the disruption of microstructural WM integrity in schizophrenia, supporting the notion that inflammation plays a regulatory role in the pathology of microstructural WM and is associated with schizophrenia.